THE ROLE OF TAXES IN SUPPORTING SUSTAINABLE DEVELOPMENT: A CRITICAL ANALYSIS - Rina Apriliani; Loso Judijanto; Melyana R Pugu (CV. Adiba Aisha Amira, 2024)
Sustainable development has become a critical global agenda in the 21st century, requiring concerted efforts across sectors to balance economic progress, environmental sustainability and social welfare. In this context, taxes present a very useful but often underutilized policy tool. The study in this research utilizes a literature review. The results indicate that to maximize the function of taxes in sustainable development, comprehensive tax reforms are needed that include: simplifying the tax system, increasing tax progressivity, strengthening tax administration, and better integration of tax policy with environmental and social policies. In addition, closer international cooperation on taxation, especially to address cross-border issues such as tax avoidance by multinational companies, is also urgently needed.